Bugsy Malone [videorecording (DVD)] - Parker, Alan, 1944-2020; Foster, Jodie; Baio, Scott; Cassisi, John, 1963-; Williams, Paul, 1940- (Paramount, 2021)
A gangster movie spoof with an all-child cast about Bugsy Malone, a boxing promoter in Prohibition-era New York City, and the battle for power between two rival mobsters.